Hadith #2217 - Sahih Muslim - S'aid bin Qays bin Qahd سعيد بن قيس بن قهد الأنصاري (Sahih Muslim)
Giving of Sadaqa is essential for every Muslim. It was said (to him): What do you say of him who does not find (the means) to do so? He said: Let him work with both his hands, thus doing benefit to himself and give Sadaqa. It was said to him: What about him who does not have (the means) to do so? He said: Then let him assist the needy, the aggrieved. It was said: What do you say of one who cannot even do this? He said: Then he should enjoin what is reputable or what is good. He said: What about
Grade: Sahih

Hadith #2782 - Sahih Muslim - S'aid bin Qays bin Qahd سعيد بن قيس بن قهد الأنصاري (Sahih Muslim)
A person came to Allah’s Apostle (ﷺ) while he was in the state of lhram. He fell down from his camel and broke his neck. Thereupon Allah’s Apostle (ﷺ) commanded to bathe him with water (mixed with the leaves of) the lote (tree), and shroud him in two (pieces of) cloth and not to apply perfume (to him), keeping his head out (of the shroud). Shu’ba said: He then narrated to me after this (the words)” keeping his head out,” his face out, for he would be raised on the Day of Resurrecti
Grade: Sahih

Hadith #4003 - Sahih Muslim - S'aid bin Qays bin Qahd سعيد بن قيس بن قهد الأنصاري (Sahih Muslim)
He who wrongly took a span of land, Allah shall make him carry around his neck seven earths.
Grade: Sahih

Hadith #4004 - Sahih Muslim - S'aid bin Qays bin Qahd سعيد بن قيس بن قهد الأنصاري (Sahih Muslim)
Leave it and take off your claim from it, for I heard Allah’s Messenger (ﷺ) as saying: He who took a span of land without his right would be made to wear around his neck seven earths on the Day of Resurrection. He (Sa’id b. Zaid) said: O Allah, make her blind if she has told a lie and make her grave in her house. He (the narrator) said: I saw her blind groping (her way) by touching the walls and saying: The curse of Sa’id b. Zaid has hit me. And it so happened that as she was walking in
Grade: Sahih

Hadith #5205 - Sahih Muslim - S'aid bin Qays bin Qahd سعيد بن قيس بن قهد الأنصاري (Sahih Muslim)
I heard Allah’s Apostle (ﷺ) as saying: Truffles are a kind of ‘Manna’ and their juice is a medicine for the eyes.
Grade: Sahih

Hadith #5208 - Sahih Muslim - S'aid bin Qays bin Qahd سعيد بن قيس بن قهد الأنصاري (Sahih Muslim)
Truffles are a kind of ‘Manna’ which Allah the Glorious and Exalted, sent down upon the people of Israil, and its juice is a medicine for the eyes.
Grade: Sahih